Acute effects of a short bout of calisthenics on mental fatigue and cognition - Tan, Gin (Nanyang Technological University, 2020)
The purpose of this study was to investigate the effects of a short bout of light-intensity calisthenics on mental fatigue and cognitive performance. Light-intensity physical activity has been found to confer beneficial physiological effects when used to disrupt sedentary periods, but less is known about its effect on cognition. A randomized-crossover mixed-design was used. The within-subjects factor was the type of break-time activity: 2 minutes of reading and calisthenics. The between-subjects factor was the participant’s sex. 32 moderately-to-highly active participants (16 Male, 16 Female; Age: 22.9 ± 1.65 yr; Body Mass Index: 21.24 ± 2.09 kg/m2) were recruited. In each session, mental fatigue was induced through a Digit Span Test (DST) followed by a break activity. At various time-points, mental state and cognitive performance was measured. For mental state, self-reporting scales for fatigue levels and the Positive and Negative Affect Schedule (PANAS) were used. For cognitive performance, a test battery consisting of Math Fluency Test (MFT), Remote Associates Test (RAT) and Stroop Test was administered. Findings showed significant interaction effects of the break activity and time-points on positive affect (PA) (p<0.001), with calisthenics conferring a greater increase as a break activity. No significant main effects were found in the other mental state and cognitive measurements. In conclusion, there is limited supporting data on the acute effects of a short bout of calisthenics exercises on mental fatigue and cognitive performance, though PA scores suggest its ability to improve moods.